Salivary Extracellular Vesicles in Detection of Head and Neck Cancers: A Systematic Review - Owecki W; Wojtowicz K; Nijakowski K (International Journal of Nanomedicine)
Wojciech Owecki,1 Karolina Wojtowicz,2 Kacper Nijakowski3 1Student’s Scientific Group in Department of Conservative Dentistry and Endodontics, Poznan University of Medical Sciences, Poznan, Poland; 2Department of Histology and Embryology, Poznan University of Medical Sciences, Poznan, Poland; 3Department of Conservative Dentistry and Endodontics, Poznan University of Medical Sciences, Poznan, PolandCorrespondence: Kacper Nijakowski, Department of Conservative Dentistry and Endodontics, Poznan University of Medical Sciences, 70 Bukowska Street, Poznan, 60-812, Poland, Email kacpernijakowski@ump.edu.plAbstract: Head and neck cancer (HNC) represents approximately 10% of all cancer cases globally, posing a significant public health challenge. Despite advances in therapeutic approaches, the mortality rate associated with HNC continues to rise. A growing body of research highlights the role of extracellular vesicles in cancer progression and pathogenesis, positioning them as promising candidates for novel biomarker discovery. Concurrently, saliva has emerged as a valuable diagnostic fluid due to its non-invasive, accessible, and cost-effective collection methods. This systematic review aims to explore the potential of salivary extracellular vesicles as diagnostic tools for the early detection and monitoring of head and neck cancer. PubMed, Scopus, Web of Science, and Embase were thoroughly searched from database inception to July 16, 2024. Twenty-three eligible studies were included, focusing on original research that described salivary extracellular vesicles as biomarkers in HNC. In oral cancer – predominantly represented by the squamous cell carcinoma subtype – several proteins, including PSB7, AMER3, and LOXL2, as well as a ten-protein panel, demonstrated strong potential as diagnostic biomarkers. Additionally, the analysis of various microRNAs (miR-140, miR-143, miR-145, miR-412-3p, miR-512-3p, miR-1307-5p) and Fourier-transform infrared (FTIR) spectra has shown promising results for oral cancer detection. For oropharyngeal cancer, lactate dehydrogenase B appears to be a promising biomarker. Another potential avenue is the assessment of human papillomavirus (HPV) risk in the development of oropharyngeal cancer. Four studies investigated HNC without specifying the cancer location; however, limited or absent reporting of sensitivity and specificity hampers the reliable evaluation of potential biomarkers. In conclusion, salivary extracellular vesicles hold promise for the detection of HNC, but further research is needed to validate their diagnostic utility.Keywords: saliva, extracellular vesicles, cancer, biomarkers, diagnosis